2001
DOI: 10.4269/ajtmh.2001.65.393
|View full text |Cite
|
Sign up to set email alerts
|

Ribodemes of Blastocystis hominis isolated in Japan.

Abstract: Abstract. To determine if genetic diversity of Blastocystis hominis exists in Japan, we monitored 64 B. hominisinfected people: 39 asymptomatic people whose infections were detected during routine medical check-ups (32 Japanese and 7 non-Japanese) and 25 patients with gastrointestinal symptoms who visited the outpatient clinics of St. Luke's International Hospital (19 Japanese and 6 non-Japanese). We detected 6 known and 2 new riboprint patterns in isolates from the infected people. There were no differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
4
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 22 publications
3
70
4
1
Order By: Relevance
“…The results are similar to some other studies performed worldwide (14,15,21,(36)(37)(38). The frequency of subtype SB83 was more than subtypes SB227 and SB340 that is similar to some other researches (5,17,20).…”
Section: Discussionsupporting
confidence: 82%
“…The results are similar to some other studies performed worldwide (14,15,21,(36)(37)(38). The frequency of subtype SB83 was more than subtypes SB227 and SB340 that is similar to some other researches (5,17,20).…”
Section: Discussionsupporting
confidence: 82%
“…In many studies, pathogenic potential of subtype 3 has been reported (16,31,(33)(34)(35). Also, some investigations have demonstrated that other subtypes such as subtype 1 were associated with symptoms (20,31,34,36).…”
Section: Discussionmentioning
confidence: 99%
“…Although these are routinely cited as a common human intestinal parasite or pathogen and have been suggested as an aetiological agent in many GI illness, including diarrhoea, inflammatory bowel disease and irritable bowel syndrome (Giacometti et al, 1999;Yakoob et al, 2004;Stark et al, 2007), it is believed that the potential pathogenicity of Blastocystis is subtype-dependent (Kaneda et al, 2001;Tan et al, 2006). Genetic and polymorphic variations of Blastocystis are well reported in the literature and classification schemes based on 18S rRNA genes and elongation factor genes have been used to infer phylogenetic relationships and discrete lineages (Ho et al, 2000;Abe, 2004;Yoshikawa et al, 2004), and the phylogenetic tree constructed from Blastocystis sequences obtained from different individuals analysed in this study falls into distinct phylogenetic clades or subtypes that have been previously defined (Arisue et al, 2003;Stensvold et al, 2007a).…”
Section: Resultsmentioning
confidence: 99%